'A MAD age': Heibon Punch, student protest, the media and consumer society in Cold War Japan. Issue 3 (2nd July 2016) - Smith, Martyn David
Abstract: In the 1960s, Heibon Punch became one of the most popular weekly magazines in Japan. It was the first weekly magazine aimed at young men and I examine here a selection of articles from the late 1960s, a period of violent student protests and international uncertainty, to argue that the importance of Heibon Punch can be found in the creation of a commodified urban, male subjectivity. In the pages of Heibon Punch, the counter-cultures that were emerging along with the protest movements taking to the streets of the major cities, became firmly embedded within the ideological state promotion of a consumer culture. The government's explicit connection of national development to domestic consumption after the ANPO protests was tied to American military and economic power, and was simply one more assault on popular sovereignty. In the pages of Heibon Punch, the political nature of the social and economic transformations wrought by high-speed economic growth was effaced by the relentless consumerisation of individual subjectivity. I place the magazine, its editorial stance and mediatisation of subjectivity, within the broader emergence of an urban, middle-class culture of consumption that served to blur the contours of individual male subjectivity, and was, in many ways, a precursor of neo-liberal subjectivities that emerged full-blown both politically and economically in the 1970s and 1980s. By pressing its readers to decide for themselves how to negotiate the identities, ideas, and goods on offer in its pages, Heibon Punch shifted the focus of political subjectivity from the established social and political system to the core of the individual subject.